Compensation of Single-Phase and Three-Phase Voltage Sag and Swell Using Dynamic Voltage Restorer - Haniyeh Marefatjou; Mohammad Sarvi (Institute of Advanced Engineering and Science, 2012)
DVR is a equipment which was connected in series and adjusting the loading voltage by feeding the voltage in system. The first installation was in 1996. usually DVR installed between sensitive loads feeder and source in distribution system .The main duty, fast support load voltage (by fast detection algorithm) during disturbance to avoid any disconnection. in this paper approaches to compensate for voltage sag and swell as a common disturbance in voltage transmission and distribution networks is presented. A dynamic voltage restorer based on the dq0 algorithm for three-phase and dynamic voltage restorer based on the average detection method for single-phase are discussed, also in this paper we compare the two methods used to compensate the single-phase and three-phase process. result of three-phase and single-phase voltage sag and swell simulation has been presented by MATLAB/SIMULINK.